1999
DOI: 10.1038/sj.gt.3301039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between cationic polymers and lipids in mediating systemic gene delivery to the lungs

Abstract: Airway inflammation frequently found in congenital and mice efficiently transfected primarily the lungs and to a acquired lung diseases may interfere with gene delivery by lesser extent, heart, spleen, kidney and liver. The other direct administration through either instillation or aerosol.vectors mediated lower to undetectable levels of luciferase Systemic delivery by the intravenous administration repexpression in the lungs, with DOTAP Ͼ GL67/DOPE Ͼ PEI resents an alternative route of delivery that might byp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(104 citation statements)
references
References 37 publications
(47 reference statements)
4
100
0
Order By: Relevance
“…We have previously shown that a single injection of DNA complexed to the cationic polymer polyethylenimine (PEI) 22K into the tail vein of adult mice efficiently transfected primarily the lung and, to a lesser extent, heart, spleen, kidney, and liver. 13 As shown in Figure 1a, the other vectors seemed to mediate lower levels of luciferase expression in the lungs, with DOTAP Ͼ PEI 25K Ͼ GL-67A. The most positive complexes gave the highest luciferase levels in the lungs and the maximal activity was obtained with PEI 22K at 15 equivalents of amino-to-phosphate (N/P) groups (corresponding to 2.4 +/− charge ratio).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously shown that a single injection of DNA complexed to the cationic polymer polyethylenimine (PEI) 22K into the tail vein of adult mice efficiently transfected primarily the lung and, to a lesser extent, heart, spleen, kidney, and liver. 13 As shown in Figure 1a, the other vectors seemed to mediate lower levels of luciferase expression in the lungs, with DOTAP Ͼ PEI 25K Ͼ GL-67A. The most positive complexes gave the highest luciferase levels in the lungs and the maximal activity was obtained with PEI 22K at 15 equivalents of amino-to-phosphate (N/P) groups (corresponding to 2.4 +/− charge ratio).…”
Section: Resultsmentioning
confidence: 95%
“…Intravenous injections of GFP-coding plasmid complexed with PEI 22K gave positive signal in the alveolar region comprising endothelial cells and pneumocytes (Figure 5a), confirming the previous observations with ␤-galactosidase transgene. 13 After an intratracheal injection, different cell targets were obtained with PEI 25K, PEI 22K, and GL-67A. PEI 25K complexes determined GFP positivity in bronchial cells (Figure 5c), with lower signal in the alveolar region (not shown).…”
Section: Localization Of Transgene Expressing Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…The stability of complexed pDNA against DNase degradation was studied by incubation of chitosan and PEI polyplexes in the presence or absence of 8 U of DNase I as described previously. 63 The reaction was carried out for 1 h at 37°C followed by examination using the agarose gel retardation assay. pDNA obtained from the stock solution was used as control.…”
Section: Stability Of Polyplexes and Pdnamentioning
confidence: 99%
“…14,26,27 The rate of injection for HSA/PEI/DNA preparations was assessed using a range of injection times between 3 s (the minimum time necessary for a single smooth i.v. push injection of 200 l via tail vein) and 5-10 l pulse injections distributed over 30 s to 3 min.…”
Section: Influence Of Injection Rate Incubation Time and Injection Vmentioning
confidence: 99%